2012
DOI: 10.1007/s11255-012-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term efficacy of levamisole in children with steroid-sensitive nephrotic syndrome

Abstract: Thus, our study showed that levamisole is a safe and effective steroid-sparing agent, with long-lasting effect even 12 months after withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…In three patients remission was maintained long after levamisole was stopped. This observation is in accordance with the results of recent studies suggesting that its steroidsparing effects last for months after its withdrawal [13, 20, 24, 25]. Boyer et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In three patients remission was maintained long after levamisole was stopped. This observation is in accordance with the results of recent studies suggesting that its steroidsparing effects last for months after its withdrawal [13, 20, 24, 25]. Boyer et al .…”
Section: Discussionsupporting
confidence: 92%
“…[25], Elmas et al . [24], and Ekambaram et al . [20] found that in some children levamisole has a long-lasting effect even 12 months after withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In 7 cohort studies (2 RCTs and 5 cohort studies), largely from Middle East countries and India, neutropenia was only reported in 8 of a total of 573 included patients in these studies. [14][15][16][17][18][19][20] Most of these studies checked the blood counts on a regular basis (biweekly or monthly), but Dayal et al 8 and Ekambaram et al 15 analyzed blood counts every 3 months. Madani et al, 17 who included the majority of the patients (304/573 patients), did not report the frequency of follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line agents are of variable effectiveness, have major potential toxicities and are not supported by robust clinical trial evidence [2]. One agent that has been shown to be effective in randomized controlled clinical trials (RCTs) in children with SSNS is levamisole [3][4][5][6][7] but there are no reports on the use of this agent in adults with nephrotic syndrome [1]. One agent that has been shown to be effective in randomized controlled clinical trials (RCTs) in children with SSNS is levamisole [3][4][5][6][7] but there are no reports on the use of this agent in adults with nephrotic syndrome [1].…”
Section: Introductionmentioning
confidence: 99%